Busting myths in online education: Faculty examples from the field. Issue 1 (28th June 2021) - Guevara, Katherine; Fattah, Layla; Ritt-Olson, Anamara; Yin, Pai-Ling; Litman, Lesley; Farouk, Samira S.; O'Rourke, Rebecca; Mayer, Richard E.
Abstract: The shift in learning environments due to the COVID-19 pandemic necessitates a closer look at course design, faculty approaches to teaching, and student interaction, all of which may predict learner achievement and satisfaction. Transitioning to an online environment requires the reinvention, reimagining, and applying of "e-flavors" of general learning theory. With this shift to online learning comes the opportunity for misunderstandings and "myths" to occur, which may stand in the way of faculty embracing online learning and fully realizing its potential. This article seeks to address several myths and misconceptions that have arisen in higher education during the rapid shift to online teaching and learning. While not comprehensive, these myths represent a snapshot of common challenges. These are we can transfer our in-person course design to online; adult learners do not need an empathetic approach; and online teaching and learning is socially isolating. Through an appreciative inquiry framework, we present each myth in the context of relevant literature and invite faculty with varied online teaching experience to share their own case studies that illustrate how they have "busted" these myths with the goal to identify existing examples of locally effective practices for the express purpose of replication that leads to positive change.